2019
DOI: 10.1161/circresaha.118.314118
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cell Therapy on Cardiovascular Outcomes in Patients With Refractory Angina

Abstract: Rationale: Cell-based therapies are a novel potential treatment for refractory angina and have been found to improve markers of angina. However, the effects on mortality and major adverse cardiac events (MACE) have not been definitively investigated. Objective: To investigate the efficacy and safety of stem cell treatment compared with optimal medical treatment for refractory angina by conducting an updated meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…As for safety, the risk of MI and stroke did not differ in patients treated with CD34 + cells with respect to placebo (odd ratio (OR) [95%CI]: 0.77 [0.36, 1.63] and 0.50 [0.08, 3.06], respectively), but, in return, the overall risk of mortality was significantly lower in CD34 + cell than in placebo group (0.24 [0.08, 0.73], p = 0.01) ( 117 ). Finally, the most updated systematic review further confirmed that CT in RA patients entails lower incidence of MACE (OR [95%CI]: 0.41 [0.25, 0.70], p < 0.0001) and all-cause mortality (0.24 [0.10, 0.60], p = 0.002) respect to placebo/controls ( 116 ). Interestingly, the subgroup analysis revealed that the favorable outcome in the pooled analysis is primarily driven by data derived from clinical studies with CD34 + cells which embody the largest patient cohort (74%) ( 116 ).…”
Section: The Case Of Cell Therapymentioning
confidence: 77%
See 3 more Smart Citations
“…As for safety, the risk of MI and stroke did not differ in patients treated with CD34 + cells with respect to placebo (odd ratio (OR) [95%CI]: 0.77 [0.36, 1.63] and 0.50 [0.08, 3.06], respectively), but, in return, the overall risk of mortality was significantly lower in CD34 + cell than in placebo group (0.24 [0.08, 0.73], p = 0.01) ( 117 ). Finally, the most updated systematic review further confirmed that CT in RA patients entails lower incidence of MACE (OR [95%CI]: 0.41 [0.25, 0.70], p < 0.0001) and all-cause mortality (0.24 [0.10, 0.60], p = 0.002) respect to placebo/controls ( 116 ). Interestingly, the subgroup analysis revealed that the favorable outcome in the pooled analysis is primarily driven by data derived from clinical studies with CD34 + cells which embody the largest patient cohort (74%) ( 116 ).…”
Section: The Case Of Cell Therapymentioning
confidence: 77%
“…Finally, the most updated systematic review further confirmed that CT in RA patients entails lower incidence of MACE (OR [95%CI]: 0.41 [0.25, 0.70], p < 0.0001) and all-cause mortality (0.24 [0.10, 0.60], p = 0.002) respect to placebo/controls ( 116 ). Interestingly, the subgroup analysis revealed that the favorable outcome in the pooled analysis is primarily driven by data derived from clinical studies with CD34 + cells which embody the largest patient cohort (74%) ( 116 ). Recently, the retrospective analysis of phase I/IIa, phase II ACT-34 and phase III RENEW was published showing that RA patients who received CD34 + cell therapy experienced the reduction of hospitalizations, cardiac procedures, and health care expenditures in the first year following treatment compared to the year prior ( 121 ).…”
Section: The Case Of Cell Therapymentioning
confidence: 77%
See 2 more Smart Citations
“…Moreover, improvements in myocardial perfusion were positively correlated with the proangiogenic growth factors, hepatocyte growth factor and platelet-derived growth factor type bb, substances involved in neovascularization, endothelial and muscle cell growth [85,86]. The most recent and the largest (8 RCTs, 526 patients) meta-analysis to date concluded that cell-based therapies improve not only indices of angina (angina episodes, Canadian Cardiovascular Society angina class, exercise tolerance, and antianginal medications), but also mortality and major adverse cardiovascular events [87,88].…”
Section: Stem Cell Therapymentioning
confidence: 99%